2010
DOI: 10.1089/fpd.2009.0506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Mycobiota and Aflatoxin Contamination of Retail Wheat Flours from Jeddah Markets

Abstract: The mycological profile of the retail wheat flour selling in different markets at Jeddah (Kingdom of Saudi Arabia) was studied. The most common genera were Aspergillus (isolated from 70% of the tested samples), Penicillium (30%), Eurotium (14%), and in a lesser extent Fusarium (20%) and Alternaria (18%). Twenty-nine strains of Aspergillus flavus were screened for their ability to produce aflatoxins (AFs). Four strains produced only aflatoxin B1 (AFB1), two strains produced AFB1 and aflatoxin B2, and one strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…The RAPD technique has been used to detect genetic variability between isolates of A. flavus and related species (Batista et al, 2008;Gehlot et al, 2011;Irshad and Nawab, 2012) and to discriminate between aflatoxigenic and non-aflatoxigenic isolates of A. flavus (Lourenço et al, 2007;Gashgari et al, 2010;Sepahvand et al, 2011). The ISSR technique has been employed to investigate the diversity and population structure of A. flavus (Tran-Dinh and Carter, 2000;Batista et al, 2008;Tran-Dinh et al, 2009;Hadrich et al, 2010;Wang et al, 2012) and to determine the similarities and dissimilarities between aflatoxigenic and non-aflatoxigenic isolates of this species (Tran-Dinh et al, 2009;Hatti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The RAPD technique has been used to detect genetic variability between isolates of A. flavus and related species (Batista et al, 2008;Gehlot et al, 2011;Irshad and Nawab, 2012) and to discriminate between aflatoxigenic and non-aflatoxigenic isolates of A. flavus (Lourenço et al, 2007;Gashgari et al, 2010;Sepahvand et al, 2011). The ISSR technique has been employed to investigate the diversity and population structure of A. flavus (Tran-Dinh and Carter, 2000;Batista et al, 2008;Tran-Dinh et al, 2009;Hadrich et al, 2010;Wang et al, 2012) and to determine the similarities and dissimilarities between aflatoxigenic and non-aflatoxigenic isolates of this species (Tran-Dinh et al, 2009;Hatti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated no relationship between RAPD profi les and severity of toxicity (35)(36)(37). In contrast, identical RAPD patterns were demonstrated in patulinproducing Paecilomyces variotii strains (38), ochratoxin A-producing Aspergillus species (39), and aflatoxins-producing A. flavus strains (40). We concluded that RAPD analysis can be used in the intraspecifi c differentiation of toxigenic P. citrinum strains obtained from air samples.…”
Section: Discussionmentioning
confidence: 69%
“…The mycological profile of wheat grains includes different genera. The most common genera are Aspergillus, Penicillium, Fusarium, and Alternaria isolated from wheat grain in Saudi Arabia (Al-Hazmi, 2010;Gashgari et al, 2010). The contamination of cereal grains by fungi is a worldwide problem, where there are several reports documenting the presence of these fungi in samples from the United States (Cleveland et al, 2003), Argentina (Roige et al, 2009), Spain (Sardiñas et al, 2011), and Algeria (Riba et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was recognized that different strains of A. flavus vary tremendously in their ability to produce AF. These results showed that total AF occurrence in wheat flour in Jeddah (Saudi Arabia) could not be a relatively critical point, regarding quality of wheat flour (Gashgari et al, 2010). Several authors have used a selective analytical method for the determination of AFs (B1, B2, G1, and G2) and residues in cereals using HPLC for low-ppb detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation